FRI0100 The Role of Insulin Resistance and Inflammation on Symmetric Dimethylarginine in Rheumatoid Arthritis. (9th June 2015) - Dimitroulas, T.; Hodson, J.; Sandoo, A.; Smith, J.; Douglas, K.; Kitas, G.
Abstract : Background: Derangement of nitric oxide (NO) metabolism is considered one of the main mechanisms through which systemic inflammation exerts deleterious effects on vascular homeostasis in rheumatoid arthritis (RA). Symmetric dimethylarginine (SDMA) indirectly inhibits NO synthesis and predicts cardiovascular (CV) and all-cause mortality in high-risk patients and general population. Objectives: We aimed to compare SDMA levels in RA patients and controls and to investigate whether SDMA is influenced by current and/or cumulative inflammatory burden as well by classical CV risk factors within RA population. Methods: 201 RA patients [155 females, median age 67 (59 – 73)] were assessed at baseline (2006). Classical CV disease risk factors were recorded and systemic inflammation was determined by the measurement of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). At follow-up (2012) routine biochemistry tests, inflammatory markers, glycemic profile and SDMA levels were measured by enzyme-linked immunosorbent assay in all patients and 82 controls [50 (60%) females, median age: 44 years (quartiles: 33 - 55)]. A quarterly measurement of CRP and ESR for each year the patient was in the study was used to produce average area under the curve (AAUC) for ESR and CRP. Paired analysis was employed for the comparison of SDMA in two groups and multivariate regression models were performed to identify predictors of SDMA. Results: SDMA was significantly lower in RA patients in both unpaired and paired analyses (p=0.001 and p=0.005 respectively) with the magnitude of the difference being similar in both models. QUICKI (p=0.005) and disease activity score-28 (p=0.007) were positively related to SDMA whistle a negative correlation was with renal function (eGFR) (p=0.005). No significant association between SDMA and cumulative inflammatory load was established in univariable multivariable analysis. SDMA levels were not found to be significantly related to CV risk factors. Conclusions: The molecular explanation of lower SDMA is unclear, but the established relationships with indices of disease activity and insulin resistance, may underline the pathogennetic role of NO pathway dysregulation in the development of atherosclerosis in RA. The biological and clinical importance of SDMA in RA remains to be evaluated in clinical and experimental studies. References: Zsuga J, Török J, Magyar MT et al. Dimethylarginines at the crossroad of insulin resistance and atherosclerosis. Metabolism 2007; 56:394-9. Schepers E, Glorieux G, Dhondt A, Leybaert L, Vanholder R. Role of symmetric dimethylarginine in vascular damage by increasing ROS via store-operated calcium influx in monocytes. Nephrol Dial Transplant 2009; 24:1429-35. Disclosure of Interest: None declared